Virtual process chain of sheet molding compound: Development, validation and perspectives. (15th July 2019) - Görthofer, Johannes; Meyer, Nils; Pallicity, Tarkes Dora; Schöttl, Ludwig; Trauth, Anna; Schemmann, Malte; Hohberg, Martin; Pinter, Pascal; Elsner, Peter; Henning, Frank; Hrymak, Andrew; Seelig, Thomas; et al.
Abstract: A virtual process chain for sheet molding compound (SMC) composites is established and validated by means of experimental investigations on a demonstrator structure. The flow in the compression molding step is simulated via a Coupled-Eulerian-Lagrangian approach using an anisotropic non-Newtonian fluid flow model. Evolution of the fiber orientation distribution (FOD) is described by Jeffery's equation. The predicted FOD is mapped to structural simulations employing a neutral data format. A mean-field anisotropic damage model is used to predict the damage evolution in the demonstrator. Simulated FOD at the end of the compression molding is validated by computer tomography. Structural simulations are validated by means of a cyclic four-point bending test on the demonstrator. The predicted results show increased accuracy with the experiments by transferring FOD data within the virtual process chain. Critical points of high damage concentrations leading to failure agree with the experimental observations.